Serum Uric Acid and Its Association with Coronary Artery Disease (Cardiovascular Journal, 2012)
Background: Few studies have assessed the relation of uric acid level with the severity of coronary  artery disease (CAD). This study investigated the association between high uric acid levels with the  presence and severity of CAD.Materials and Methods: This study was designed as an observational cohort study. The study was  composed of 180 patients admitted at our institution due to symptoms related to CAD. Patients  having angiographic evidence of stenosis in coronary artery were as case group and without stenosis  control group. Patients with high uric acid (hyperuricemia) were defined as serum uric acid  concentration ?7.0mg/dl or ?420 ?mol/L in men and ?6mg/dl or ?360 ? mol/L in women. The  presence of CAD has been defined as the Gensini score being ?1.  Results: There was a statistically significant difference between the mean uric acid levels of patients  with and without CAD (358.23±71.11 ?mol/l vs251.32±54.92 ?mol/l respectively, p